Pendidikan Islam Terpadu sebagai Solusi Problematika Dikotomi Ilmu - Yelita Azizah; Badoar Hasibuan (KAMPUS AKADEMIK PUBLISING, 2026)
This study was motivated by the phenomenon of character degradation among students and the persistent dichotomy between religious and secular knowledge in the Indonesian education system, which has resulted in a generation that is intellectually superior but morally and spiritually weak. The purpose of this study is to analyze the concept of integrated Islamic education and its urgency as a solution to overcome the dichotomy between knowledge and strengthen character building. The method used is a qualitative descriptive approach with a library research type of study, through the collection and review of data from books, journals, and relevant scientific sources. The results of the study show that integrated Islamic education combines Islamic values with general knowledge in a unified curriculum, method, and educational environment, thereby optimizing the cognitive, affective, and psychomotor domains of students in a balanced manner. Integrated Islamic education also emphasizes the integration of aqliyah, ruhiyah, and jasadiyah education, as well as involving the synergistic roles of schools, families, and communities. In conclusion, integrated Islamic education is a strategic alternative in overcoming the dichotomy of knowledge and building a Muslim generation that is faithful, has noble character, and is competent in facing the challenges of the times.